Serum selenium concentration in patients with autoimmune thyroid disease - Delyana M. Davcheva; Gergana K. Kirova; MariaMaria Zh. Miteva; Todorka Z. Tzvetkova; Maria M. Orbetzova; Boyan I. Nonchev; Kiril K. Simitchiev; Veselin J. Kmetov (Folia Medica, 2022)
Abstract Introduction: Selenium (Se) is one of the environmental factors with an essential role in the pathogenesis of autoimmune thyroid disease (ATD). Scarce data is available for the selenium status of the Bulgarian population especially for patients with thyroid disorders. Aim: To compare the serum selenium (s-Se) concentrations in patients with ATD and healthy controls from Bulgarian population. Materials and methods: The s-Se concentrations were measured in 105 patients newly diagnosed or untreated for the previous 6 months with ATD (mean age 44±13 years). The patients were divided into three groups: euthyroid autoimmune thyroiditis (AIT) (n=31), hypothyroid AIT (n=33), and hyperthyroid patients with AIT or Graves’ disease (GD) (n=41). The results were compared to s-Se concentrations in 40 age- and sex-matched healthy controls. Determination of s-Se was carried out by inductively coupled plasma mass spectrometry (ICP-MS) after microwave-assisted acid mineralization of the serum samples. Results: The s-Se concentrations in patients with hyperthyroidism were significantly lower than those in the control group (hyperthyroidism: 69±15.0 µg/L vs. controls: 84±13 µg/L, p<0.001). There was no significant difference in the s-Se concentrations between euthyroid and hypothyroid participants with AIT and healthy controls. The s-Se concentrations in our control individuals were within the range of 53-137 µg/L, reported in literature data on mean serum and plasma levels of European healthy adults. Conclusions: The mean s-Se concentrations observed in all groups were below or close to the cutoff value of 80 µg/L, considered optimal for the activity of the Se-dependent antioxidant systems.